Taxonomic Identification of Two Poorly Known Lantern Shark Species Based on Mitochondrial DNA From Wet-Collection Paratypes - Agne, Stefanie; Naylor, Gavin J. P.; Preick, Michaela; Yang, Lei; Thiel, Ralf; Weigmann, Simon; Paijmans, Johanna L. A.; Barlow, Axel; Hofreiter, Michael; Straube, Nicolas (Frontiers in Ecology and Evolution, 2022)
Etmopteridae (lantern sharks) is the most species-rich family of sharks, comprising more than 50 species. Many species are described from a few individuals, and re-collection of specimens is often hindered by the remoteness of their sampling sites. For taxonomic studies, comparative morphological analysis of type specimens housed in natural history collections has been the main source of evidence. In contrast, DNA sequence information has rarely been used. Most lantern shark collection specimens, including the types, were formalin fixed before long-term storage in ethanol solutions. The DNA damage caused by both fixation and preservation of specimens has excluded these specimens from DNA sequence-based phylogenetic analyses so far. However, recent advances in the field of ancient DNA have allowed recovery of wet-collection specimen DNA sequence data. Here we analyse archival mitochondrial DNA sequences, obtained using ancient DNA approaches, of two wet-collection lantern shark paratype specimens, namely Etmopterus litvinovi and E. pycnolepis, for which the type series represent the only known individuals. Target capture of mitochondrial markers from single-stranded DNA libraries allows for phylogenetic placement of both species. Our results suggest synonymy of E. benchleyi with E. litvinovi but support the species status of E. pycnolepis. This revised alpha level taxonomy is helpful for future conservation and management efforts, as our results indicate a larger distribution range of E. litvinovi. This study further demonstrates the importance of wet-collection type specimens as genetic resource for taxonomic research.